Socioeconomic and psychological dimensions of utilizing indigenous knowledge in paddy and other field crop (ofc) farming in trincomalee district, sri lanka - Mihirani, P.M.N.; Weerakoon, W.R.W.M.A.P.; Weerakoon, W.R.W.M.S.N.P; Withana, N.R.P; Dharmawardhana, M.W.C (University of Jaffna, 2016)
Application of modern expertise is currently debatable in the context of Sri Lankan agriculture where, inapt use farm inputs and cultivation schedules have caused severe ecological and health issues. Consequently, approaches allied to Indigenous knowledge (IGK) receive great attention as a potential solution. This study appraised a range of qualitative and quantitative aspects of IGK to reach the objectives of assessing (1) self reported knowledge, perceptions and attitudes of farmers on IGK, (2) current use of IGK in farming, and (3) factors that are vital for the use of IGK. Questionnaire-based interviews (n=500) were held in five DS divisions in Trincomalee District in 2015 across major ethnic groups in “Major” and “Minor” irrigation systems. The results presage that the existing IGK systems are alarmingly receding where self-reported knowledge of farmers was desolately frail. The perceptions and attitudes were off-putting though a few have used IGK related methods under the direction of government institutions. Knowledge, awareness, age, experience, beliefs, social cohesion, locus of control and government support were identified to have effects on the use of IGK. The involvement of clued-up farmers in training, research and collective farming programs whereas an improved national policy, inter-ethnic cohesion and communiqué channels via strong government intervention are required to streamline dissemination and application of IGK among all ethnic groups.
Keywords: Indigenous knowledge; Traditional farming; Sri Lankan agriculture